Quantitative modeling of DNA–protein interactions: effects of amino acid substitutions on binding specificity of the Mnt repressor - Man, Tsz-Kwong (Oxford University Press, 2004)
Understanding DNA–protein recognition quantitatively is essential to developing computational algorithms for accurate transcriptional binding site prediction. Using a quantitative, multiple fluorescence, relative affinity (QuMFRA) assay, we determine the binding specificity of 11 different position 6 variants of the Mnt repressor for operators containing all 16 possible dinucleotides at operator positions 16 and 17. We show that the wild-type and all variant proteins interact with the two positions in a non-independent manner, but that a simple independent model provides a close approximation to the true binding affinities. The wild-type His at amino acid 6 is the only protein to prefer the AC sequence of the wild-type operator, whereas most of the variant proteins prefer TA. H6R is unique in having a strong preference for C at position 16. A comparison of the quantitative binding data for all of the protein variants with a model for recognition of the early growth response (EGR) zinc finger family suggests that interactions of Mnt with positions 16 and 17 are similar to interactions of EGR with positions 1 and 2, respectively. This information leads to an augmented model for the interaction of Mnt with its operator.